Learning styles of nurse anesthesia students related to level in a master of science in nursing program. - Sherbinski L (AANA Journal, 1994)
To alleviate the shortage of anesthetists, nurse anesthesia programs are expanding and new programs are being developed while they simultaneously move into the master's degree framework. Students' learning style preferences can provide valuable information for educators engaged in facilitating and enhancing learning. This study identified the learning styles of nurse anesthesia students enrolled in 12 programs that confer a master of science in Nursing degree in relation to the students' gender and level in an anesthesia program. Learning profiles were determined by scores on the Learning Style Inventory (Kolb, 1985). A personal data sheet was used to elicit the students' demographic characteristics. Surveys were administered to a sample of 264 nurse anesthesia students, with 164 usable responses (62.8%). Results indicated a preference for the assimilator learning style (37.2%). A statistically significant relationship between learning style and level in an anesthesia program was found (chi-square = 11.14, df = 3, P < .05). Whereas students who had completed fewer than 12 months in an anesthesia program showed no dominant preference for a learning style, students who had completed more than 12 months were predominantly distributed in two learning style categories: assimilators (40.0%) and convergers (38.8%). No statistically significant relationships were identified between learning styles and gender.